COVID-19 governance and decision-making at provincial level in South Africa - Godwell Nhamo; Gideon W. Mutanda (Cogent Social Sciences, 2024)
Globally, there is an unequivocal call to promote good governance at all levels of government through the promotion and development of transparent, effective and accountable institutions. These perspectives remain to be investigated concerning COVID-19 governance at provincial level in South Africa, where provinces play a ‘midwife’ role between national and local government spheres. With new institutions created, and existing ones buttressed, voices from government officials and citizens should be heard on how the government managed the pandemic. This paper mainly investigates the perspectives of government officials on the effectiveness of COVID-19 governance in Limpopo Province. It also assesses how households and other stakeholders evaluated the effectiveness of COVID-19 governance and responded to the measures put in place by the government. The work utilised five complementary surveys from government officials, households, agriculture, education sector, and the mining sector. The findings are that the Limpopo government COVID-19 governance model resembled a hybrid, drawing components from the agile and adaptive, as well as the whole-of-society and whole-of-society models. Non-pharmaceutical interventions worked, and the rolling out of vaccines went well, with 73–84% of respondents across the surveys having been fully vaccinated. The Limpopo government did well to discourage unproven treatments, including malaria and ivermectin tablets. However, corruption in procurement was reported following the relaxation of regulations to permit emergency procurement by the National treasury. Moving forward, the work recommends that if future pandemics and/or other disasters emerged, the governance model used remains and get enhanced if need be. Flexible, yet stringent procurement protocols need to be developed. Government needs to swiftly move to embrace non-conventional (informal) disaster risk reduction measures.